Open Campuses for the Elite and Restricted Campuses for Others : Class Segregation in Public Higher Education During the Covid-19 Shutdown (Higher Education Politics and Economics, 2025)
Segregation is often seen in terms of race. However, it can also be based on socioeconomic status. Public colleges and universities in the U.S. had highly divergent responses to the Covid-19 pandemic. Despite operating under similar health and legal considerations, campuses at most elite institutions were treated as essential functions while the neighboring campuses of less elite institutions were often treated as non-essential functions. This was problematic during the pandemic, but the discrimination appears to be continuing after the emergency has passed. The policy of continued reduction of the role of the college campus is an attractive option for less exclusive institutions. While a campus is most valuable for the more marginalized students, it is their campuses that closed and remain limited. The community college campus is the foundation of higher education for many students. The purpose of this paper was to explore the value of the campus experience.